A Survey of Hedge and Safe Havens Assets against G-7 Stock Markets before and during the COVID-19 Pandemic - Huseyin Ozdemir; Zeynel Abidin Ozdemir (Institute of Labor Economics (IZA), 2021)
We propose a new Sharpe ratio index obtained from return and volatility spillover indices to individual assets from the whole financial system. We use our new approach to shed light on a new perspective on a hot topic examining the safe-haven assets after Covid-19. To do that, we compare both hedge and safe-haven properties of gold, Bitcoin, and crude oil against G-7 stock markets by using daily return and volatility data from September 2013 to October 2021. Our empirical findings show that the hedging effectiveness of gold, Bitcoin, and crude oil varies overtime before the Covid-19 pandemic. Furthermore, according to our analysis results, only Bitcoin acts as a safe haven against G-7 stock markets during most of the Covid-19 pandemic time.
Keywords: C58; G10; 330; sharpe ratio; safe haven; hedge; spillover effect; G-7 countries